2015
DOI: 10.1002/fsn3.247
|View full text |Cite
|
Sign up to set email alerts
|

Frying stability of sunflower oil blended with jujube (Ziziphus mauritiana Lam.) leaf extract

Abstract: The aim of present study was to compare the effects of ultrasound‐assisted and microwave‐assisted extraction with solvent extraction method on antioxidant activities of jujube (Ziziphus mauritiana Lam.) leaf extracts in stability of sunflower oil during deep frying. The antioxidant activities of the extracts were evaluated by using 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH˙) radical scavenging and β‐carotene bleaching assays. Ultrasound‐assisted extraction was the most effective method on antioxidant activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…The results of the current study were in good agreement with Delfanian et al . () who reported that sunflower oil treated with BHT resulted in significantly ( P < 0.05) lower CDV than control sample (without BHT). In another research, higher polyphenol amount was noted for microwave‐irradiated virgin olive oils than conventionally heated virgin olive oils (Brenes et al ., ).…”
Section: Resultsmentioning
confidence: 95%
“…The results of the current study were in good agreement with Delfanian et al . () who reported that sunflower oil treated with BHT resulted in significantly ( P < 0.05) lower CDV than control sample (without BHT). In another research, higher polyphenol amount was noted for microwave‐irradiated virgin olive oils than conventionally heated virgin olive oils (Brenes et al ., ).…”
Section: Resultsmentioning
confidence: 95%
“…Results obtained with Ziziphi spinosae semen oil agree with similar studies on other Ziziphus species. Mojtaba et al., [ 31 ] showed that sunflower oil containing 500 and 700 ppm extract of jujube leaf had a pronounced effect on resisting the formation of polar compounds. The results of another investigation indicated that soybean oil with 600 ppm extract of jujube fruit has a higher t 24 value than 100 ppm TBHQ.…”
Section: Resultsmentioning
confidence: 99%
“…marker for major oil degradation and it is adequate at maximum of 25-27 for used frying oil 21 . The fresh soybean oil had a TPM content of 5.6 , reflecting the good quality of the oil used, as TPM content of unused oils normally ranges between 0.4 -6.4 27 . The TPM was found to increase during frying and had high correlation coefficient with heating time 28 .…”
Section: Effect Of Purslane Leaves Extract Oil Stabilitymentioning
confidence: 99%